Determination Of Aerosol Optical Thickness From Spectral Sky Transmittance. - H., S. Lim; MatJafri, M. Z.; Abdullah, K.; Saleh, N. M.; Al Sultan, Sultan (2004)
The objective of this study is to test the feasibility of the proposed technique for retrieving spectral aerosol optical thickness (AOT) from the spectral transmittance measurements. The measurements have been acquired around Penang Island, Malaysia. Ground-based measurements were made with a handheld spectroradiometer. The measured spectral transmittance data were then converted to AOT values 6 spectral bands between 400 and 900 nm. Spectral AOT maps were generated using Kriging interpolation method for the 6 spectral bands. Air quality map was produced using this technique.